Citizenship (Amendment) Act, 2019: The Politicization of Religious Identity in Contemporary India - Amelia, Adhenna Zakia; Kartini, Evida (UI Scholars Hub, 2023)
The victory of the Bharatiya Janata Party (BJP) in the 2014 and 2019 elections with Narendra Modi as prime minister of India is a crucial momentum for the revival of Hindu nationalism in India. Allegations of the politicisation of religion were growing under Modi's leadership with various controversial policies, one of which was the Citizenship (Amendment) Act (CAA) that was passed in 2019. This policy accelerates the granting of citizenship status to Hindu, Sikh, Buddhist, Jain, Parsi, and Christians, immigrants from Afghanistan, Bangladesh, and Pakistan. This paper discusses how the BJP's politicisation of religious identity impacts policy outcomes within the context of the CAA. We argue that the BJP's alignment with the Sangh Parivar and the utilisation of religious identity as a political tool has led to the prioritisation of Hindu interests in policies, disproportionately affecting minority communities, particularly Muslims. The study highlights how the BJP strategically used the CAA, triggering counter-mobilisation from the Muslim community, which, coupled with the government's response, intensified communal tensions. The BJP's success in leveraging its popularity to advance its agenda, including implementing the CAA, exacerbated perceived threats among Hindu voters and fueled political mobilisation. The paper emphasises that in a democratic context like India, political parties aligning with religious identities can secure support and provoke conflicts.